1971
DOI: 10.1128/aem.21.2.350-357.1971
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics of Cloned Populations of Herpes Simplex Virus Types 1 and 2

Abstract: By using cloned types 1 and 2 herpes simplex virus, obtained by selecting large and small plaques produced by material from human lesions, studies were performed to compare properties between preparations of each type. Regarding the rate of inactivation by ultraviolet light, no differences were found between the two antigenic types and none between the preparations obtained from either type. In contrast, type 1 preparations were found to be more readily inactivated at 45 C than type 2. Plaque size of cloned pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1972
1972
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…Whether this antigenic difference is of sufficient magnitude and stability to warrant "type" distinctions is a matter of present controversy (6,9). Although antigenic character does not appear to vary with EOP in this or another study (8), or with other markers (12,13), there is great diversity in the degree of relatedness between strains within groups. Hampar et al (6) have suggested that H. hominis strains should be classified into one serological group as a species by the use of 7S antibodies and that late 19S antibodies should be used for determining subtypes within that species.…”
Section: Discussioncontrasting
confidence: 51%
“…Whether this antigenic difference is of sufficient magnitude and stability to warrant "type" distinctions is a matter of present controversy (6,9). Although antigenic character does not appear to vary with EOP in this or another study (8), or with other markers (12,13), there is great diversity in the degree of relatedness between strains within groups. Hampar et al (6) have suggested that H. hominis strains should be classified into one serological group as a species by the use of 7S antibodies and that late 19S antibodies should be used for determining subtypes within that species.…”
Section: Discussioncontrasting
confidence: 51%
“…Monolayers were infected at an MOI of 0.1, and supernatants were harvested after 2 to 3 days at 34°C, when almost total cytopathic effect was evident. Fluids were clarified by centrifugation, and the titers were determined on Vero cell monolayers (28).…”
Section: Methodsmentioning
confidence: 99%
“…Cells and fluids from triplicate wells were harvested at designated times postinfection and stored at -700C. Plaque titrations were done with the use of Vero cell monolayers (28).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations